Involvement of PI3K/HIF-1α/c-MYC/iNOS Pathway in the Anticancer Effect of Suaeda vermiculata in Rats - Hamdoon A. Mohammed; Mohamed G. Ewees; Nesreen I. Mahmoud; Hussein M. Ali; Elham Amin; Mohamed S. Abdel-Bakky (MDPI AG, 2023)
Suaeda vermiculata Forssk. ex JF Gmel. (SV), a traditional known plant, has shown in vitro cytotoxic activity against HepG2 and HepG-2/ADR (doxorubicin-resistant cells) liver cell carcinoma cell lines, as well as hepatoprotection against paracetamol and carbon tetrachloride (CCl4)-induced liver injury. The current study evaluated the protective effect of SV, administered against N-diethylnitrosamine (NDEA)-induced HCC in rats. The possible modulatory effect of SV on the PI3K/HIF-1α/c-MYC/iNOS pathway was investigated. Sixty male adult albino rats (200 ± 10 g) were equally classified into five groups. Group I served as a control; Group 2 (SV control group) received SV (p.o., 200 mg/kg body weight); Group 3 (NDEA-administered rats) received freshly prepared NDEA solution (100 mg/L); and Groups 4 and 5 received simultaneously, for 16 weeks, NDEA + SV extract (100 and 200 mg/kg, orally). NDEA-treated rats displayed significant increases in serum levels of AFP, CEA, PI3K, malondialdehyde (MDA), epidermal growth factor receptor (EGFR), and vascular endothelial growth factor (VEGFR), with increased liver tissue protein expression of fibrinogen concomitant and significantly decreased concentrations of antioxidant parameters (catalase (CAT), superoxide dismutase (SOD), and reduced glutathione (GSH)) in comparison to normal rats. On the flip side, AFP, CEA, PI3K, MDA, EGFR, and VEGFR serum levels were significantly reduced in rats that received NDEA with SV, both at low (SV LD) and high (SV HD) doses, accompanied by significant improvements in antioxidant parameters compared to the NDEA-treated group. Conclusions: SV possesses a significant hepatoprotective effect against NDEA-induced HCC via inhibiting the PI3K/HIF-1α/c-MYC/iNOS pathway, suggesting that SV could be a promising hepatocellular carcinoma treatment.